No Little Feet: Managing Pseudocyesis in a Homeless, Acutely Manic Patient with Schizoaffective Disorder, Bipolar Type - Talitha West; Omotola Ajibade; Anthony Fontanetta; Samreen Munir (Case Reports in Psychiatry)
Pseudocyesis is a complex psychiatric manifestation of the physical symptoms of pregnancy. Although not pregnant, the pseudocyetic patient displays signs and symptoms consistent with pregnancy, such as abdominal distention, cramping, and/or sensations of fetal movement. Pseudocyesis is more common in developing countries than in the developed world, possibly due to the importance that traditional societies attach to childbearing and the low social status that these societies assign to women who are unable to produce children. Socioeconomically disadvantaged women in developed countries may also be at increased risk. Although the etiology, pathogenesis, diagnosis, and management of pseudocyesis are poorly understood, it manifests with real symptoms, which may complicate both the patient’s perspective about her condition and the medical and psychiatric teams’ approach to the patient. This case report is one of only a few in the literature to present an example of pseudocyesis developing in the context of acute mania. After describing the patient’s clinical course, from her initial symptoms of pseudocyesis to their eventual resolution, this report will provide recommendations for the sensitive care of patients with this rare but significant condition.